2017
DOI: 10.1007/s10616-017-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of antibody concentration and achievement of high cell density CHO cell cultivation by adding nucleoside

Abstract: Recently, with the dramatic increase in demand for therapeutic antibodies, Chinese hamster ovary (CHO) cell culture systems have made significant progress in recombinant antibody production. Over the past two decades, recombinant antibody productivity has been improved by more than 100-fold. Medium optimization has been identified as an important key approach for increasing product concentrations. In this study, we evaluated the effects of deoxyuridine addition to fed-batch cultures of antibody-expressing CHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
(43 reference statements)
2
27
0
Order By: Relevance
“…Higher titers continue to be reported in recent literature (e.g. 9-10 g/L titer in 14-18 days) (Handlogten et al 2018;Huang et al 2010;Takagi et al 2017), suggesting that potential remains for further increases in productivity and reduction in cost using fed-batch operation.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Higher titers continue to be reported in recent literature (e.g. 9-10 g/L titer in 14-18 days) (Handlogten et al 2018;Huang et al 2010;Takagi et al 2017), suggesting that potential remains for further increases in productivity and reduction in cost using fed-batch operation.…”
Section: Introductionmentioning
confidence: 61%
“…Overall, limited literature is available for fed-batch process development with very high (~ 10 g/L) fed-batch titers. Since 10 g/L titer on Day 18 for two proteins was reported for the first time (Huang et al 2010), 9-10 g/L titers were reported for production of one mAb on Day 14 or Day 16 in two other case studies (Handlogten et al 2018;Takagi et al 2017). Conventional SDs of ≤ 1.5 × 10 6 cells/mL were used in the above literature.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementing the selection media with nucleosides improved nucleotide and DNA synthesis, enhancing cell growth and recovery. Similarly, a recent study has indicated that supplementing nucleosides to the fed‐batch cultures increased CHO cell growth and in turn achieve higher titer …”
Section: Discussionmentioning
confidence: 90%
“…Chen et al illustrated that hypoxanthine and thymidine can promote initial cell growth and volumetric production of mAb without effects on long-term stability of antibody-producing CHO cells (Chen et al 2011). Deoxyuridine were observed to increase the mAb concentration to 5.5 g/L compared with 3.3 g/L of no addition of deoxyuridine, and there were no significant differences in the specific production rate (Takagi et al 2017). In terms of mAb's quality, it was clarified that feeding of uridine, galactose and manganese chloride can increase the galactosylation level (Gramer et al 2011).…”
Section: Introductionmentioning
confidence: 86%